GREEN SYNTHESIS OF SILVER NANOPARTICLES USING GALIUM VERUM L. AQUEOUS EXTRACT AND EVALUATION OF ITS ANTIMICROBIAL ACTIVITY - ANDREICA, Adriana-Maria; VLASSA, Mihaela Cecilia; CARPA, Rahela; PETEAN, Ioan (Studia Universitatis Babeș-Bolyai Chemia, 2025)
The development of cost-efficient and sustainable methods for the synthesis of nanomaterials still remains a scientific challenge. The aim of this study was to investigate the green synthesis of silver nanoparticles using aqueous extract of Galium verum L. (GV) as a potential source of biomolecules able to reduce the silver ions and stabilize them. Reaction parameters such as concentrations of AgNO3, extract to AgNO3 ratio, temperature, pH, and reaction time were optimized. The synthesis of silver nanoparticles (GV-AgNPs) using different parameters was monitored by ultraviolet-visible spectroscopy (UV-Vis). Fourier transform infrared spectroscopy (FTIR) results showed the presence of functional groups that act as reducing agents and stabilize the GV-AgNPs. Atomic force microscopy (AFM) confirmed that the particles were round-shaped with a diameter of about 25 nm. The GV-AgNPs show different antimicrobial activity depending on the type of sample and depending on the microbial strain tested.